2012
DOI: 10.1038/srep00875
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modularity in ERα Transcriptional Network Is Associated with Distinct Functions and Implicates Clinical Outcomes

Abstract: Recent genome-wide profiling reveals highly complex regulation networks among ERα and its targets. We integrated estrogen (E2)-stimulated time-series ERα ChIP-seq and gene expression data to identify the ERα-centered transcription factor (TF) hubs and their target genes, and inferred the time-variant hierarchical network structures using a Bayesian multivariate modeling approach. With its recurrent motif patterns, we determined three embedded regulatory modules from the ERα core transcriptional network. The GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…New advances in network modeling allow for networks to be tested, quantified, and corrected (Sayyed-Ahmad et al, 2007). Time-course expression data in particular can capture dynamic properties of transcriptional networks that steady-state transcript measurements cannot (Nelson et al, 2004; Opper and Sanguinetti, 2010), and even time-course ChIP-seq data has been introduced into network models (Tang et al, 2012). Arabidopsis and Zinnia transdifferentiation systems are potentially useful models for generating time-course transcript data relating to SCW regulation, but existing time-course data (e.g., Kubo et al, 2005; Yamaguchi et al, 2011) lacks the temporal resolution to test and model the dynamic behavior of the SCW transcriptional network.…”
Section: The Scw Transcriptional Network: Structure Evolution and Dmentioning
confidence: 99%
“…New advances in network modeling allow for networks to be tested, quantified, and corrected (Sayyed-Ahmad et al, 2007). Time-course expression data in particular can capture dynamic properties of transcriptional networks that steady-state transcript measurements cannot (Nelson et al, 2004; Opper and Sanguinetti, 2010), and even time-course ChIP-seq data has been introduced into network models (Tang et al, 2012). Arabidopsis and Zinnia transdifferentiation systems are potentially useful models for generating time-course transcript data relating to SCW regulation, but existing time-course data (e.g., Kubo et al, 2005; Yamaguchi et al, 2011) lacks the temporal resolution to test and model the dynamic behavior of the SCW transcriptional network.…”
Section: The Scw Transcriptional Network: Structure Evolution and Dmentioning
confidence: 99%
“…Therefore, identification of regulatory modules and gene networks is critical for understanding molecular mechanisms of transcriptional regulation in complex biological systems. Various mathematical algorithms or computational methods have been developed for integrative analysis of microarray gene expression and TF binding data to predict target genes of TFs, such as Bayesian hierarchical network [1], Bayesian multivariate modeling [2], matrix decomposition [3] and regression model [4]. Based on predicted target genes of multiple TFs, we can unravel transcriptional regulatory modules and reconstruct gene networks.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is considerable evidence that estrogens are also mammary carcinogens in the breast, involving the metabolism of estrogen to genotoxic, mutagenic metabolites and the stimulation of tissue growth [50]. For instance, ERα, an estrogen-inducible transcription factor, is member of the nuclear receptor super family, the dysfunction of which accounts for 70% breast tumors [71]. Indeed, clinical and experimental studies have suggested an important role for Estrogen signaling pathway in the treatment of breast cancer and the reduction for estrogen deprivation of mammary tumors [70].…”
Section: Resultsmentioning
confidence: 99%